Diagnostic Utility of Procalcitonin and C-Reactive Protein in Detection of Bacterial Infection in Patients of Abdominal Sepsis - Mahuli, Kshiti; Mahakalkar, Chandrashekhar; Jajoo, Suhas; Patil, Deepak; Aravind, Chava; Anil Reddy, Cherkula (Journal of Neonatal Surgery, 2025)
Background: The diagnostic utility of Procalcitonin (PCT) and C-Reactive Protein (CRP) as biomarkers for bacterial infection in patients with abdominal sepsis is of significant interest due to the critical nature of timely and accurate sepsis diagnosis. Methods: This cross-sectional study included 120 patients presenting with symptoms of abdominal sepsis. We evaluated the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of PCT and CRP, and analyzed their correlation with the severity of sepsis. Results: The mean age of the study subjects was 39.47 years, predominantly male (72.50%). PCT demonstrated a sensitivity of 85% and a specificity of 90%, while CRP showed a sensitivity of 80% and a specificity of 85%. The biomarkers correlated strongly with sepsis severity, indicating higher values in more severe cases. Conclusion: PCT and CRP are valuable biomarkers for diagnosing bacterial infection in abdominal sepsis, with PCT showing slightly higher diagnostic accuracy than CRP.